The Computational Efficiency of the Ji-Lee-Li Algorithm for the Assignment Problem - Goldengorin, Boris; Jäger, Gerold (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2008)
Ji et al. have conjectured that using the matrix form (to represent a basic solution) instead of the Simplex tableau in the dual Simplex method will lead to an algorithm with the time complexity comparable to the Hungarian algorithm for solving the Assignment Problem. In this note we show that both the time complexity and the CPU times of the Ji et al. algorithm are far away from being competitive to the Hungarian algorithm.